How can Indonesia become a truly prosperous country? An exploration from an accounting perspective. - Teguh, Iman (Jurnal Riset Akuntansi Terpadu, 2024)
The purpose of this study is to provide enlightenment for Indonesia to become a truly prosperous country based on an accounting perspective. This research used an exploratory approach to achieve the research objective. The research sample of this study includes most liveable cities in the world and most liveable cities in Indonesia. The research uses nineteen indicators from six dimensions of the financial condition of local government to explore. The results indicate that Indonesia can become a truly prosperous country if local governments in Indonesia can increase the productivity of cash and cash equivalents that are still idle to improve the quality of public services. Regional governments in Indonesia can use long-term debt mechanisms, maintain financial management patterns in operational activities every fiscal year, continuously explore potential regional income sources, maintain financial flexibility management patterns, and increase per capita spending allocations. The result of this research provides practical implications for local governments in Indonesia in realizing the goal of statehood to become a truly prosperous Indonesia. The originality of this research is to explore the financial condition of local governments to make Indonesia a truly prosperous country.